2023
DOI: 10.1093/jxb/erad005
|View full text |Cite
|
Sign up to set email alerts
|

Plasmopara viticolaRxLR effector PvAvh77 triggers cell death and governs immunity responses in grapevine

Abstract: Grapevine downy mildew, caused by the oomycete Plasmopara viticola, is one of the most considerable production challenges for the grape and wine industries. P. viticola injects a plethora of effectors into host cells to disrupt immune processes, but the mechanisms by which these effectors act at the molecular level have not been well characterized. Herein, we show that a candidate P. viticola Avirulence Homolog (Avh) RxLR effector gene, designated PvAvh77, was strongly up-regulated during the initial stages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Our previous study identified that PvAvh77‐M2 is a deletion mutation of P. viticola RxLR effector PvAvh77, whose purified protein is able to elicit immune responses in the apoplast (Fu et al., 2023). To investigate whether the purified protein of PvCRN11 can also initiate plant immunity in the apoplast, we purified the PvCRN11 protein using a prokaryotic expression system.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study identified that PvAvh77‐M2 is a deletion mutation of P. viticola RxLR effector PvAvh77, whose purified protein is able to elicit immune responses in the apoplast (Fu et al., 2023). To investigate whether the purified protein of PvCRN11 can also initiate plant immunity in the apoplast, we purified the PvCRN11 protein using a prokaryotic expression system.…”
Section: Resultsmentioning
confidence: 99%
“…Here, similarly to other pathogenic oomycetes, the causative agent of grapevine downy mildew pathogen, P. viticola , produces a repertoire of effectors that are essential for its virulence and pathogenicity (Lan et al., 2019; Lei et al., 2019; Liu, Chen, Ma, et al., 2021; Liu, Chen, Yin, et al., 2021; Ma, Chen, et al., 2021; Xiang et al., 2022; Yin et al., 2022). Although the P. viticola effector PvAvh77 stimulates immune responses in plant apoplast, transient expression of it intracellularly also suppresses plant immunity and promotes pathogen infection (Fu et al., 2023). However, cases have also been reported in which P. viticola effectors can stimulate plant immunity and promote disease resistance in plants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations